PAKC: A novel panel of HLA class I antigen presentation machinery knockout cells from the same genetic origin. Issue 3 (1st February 2021) - de Waard, Antonius A.; Verkerk, Tamara; Jongsma, Marlieke L. M.; Hoefakker, Kelly; Sethumadhavan, Sunesh; Gerke, Carolin; Bliss, Sophie; Kong, Xiangrui; Janssen, George M. C.; de Ru, Arnoud H.; Claas, Frans H. J.; Mulder, Arend; et al.
Abstract : A single model system for integrative studies on multiple facets of antigen presentation is lacking. PAKC is a novel panel of ten cell lines knocked out for individual components of the HLA class I antigen presentation pathway. PAKC will accelerate HLA‐I research in the fields of oncology, infectiology, and autoimmunity.